Chitosan and its derivatives regulate lactic acid synthesis during milk fermentation - Kurchenko, Vladimir; Halavach, Tatsiana; Yantsevich, Alexey; Shramko, Mariya; Alieva, Lyudmila; Evdokimov, Ivan; Lodygin, Alexey; Tikhonov, Vladimir; Nagdalian, Andrey; Ali Zainy, Faten M.; AL-Farga, Ammar; ALFaris, Nora Abdullah; et al. (Frontiers in Nutrition, 2024)
This study presents the results of a comparative study of the effect of oligochitosans and chitosan on the lactic acid fermentation process during cultivation of Lactobacillus delbrueckii subsp. bulgaricus (L. bulgaricus) and long-term storage. Depending on the molecular weight, concentration, and molecules size of oligochitosans and chitosan effect on lactic acid synthesis during cultivation of L. bulgaricus and long-term storage of the fermented dairy product. The results of the study showed that when L. bulgaricus was cultured in the presence of 25.4 kDa oligochitosans at concentrations of 0.0025%, 0.005%, 0.0075% and 0.01%, the average rate of LA synthesis over 24 hours was 11.0×10 - 3 mol/L/h, 8.7×10 -3 mol/L/h, 6.8×10 -3 mol/L/h, 5.8×10 -3 mol/L/h, respectively. The 45.3 kDa oligochitosans had a similar effect, while the average rate of lactic acid synthesis in the control sample was only 3.5×10 -3 mol/L/h. Notably, 350 kDa chitosan did not affect the rate of lactic acid synthesis compared with the control sample. It was found that different mechanisms of action of oligochitosans and chitosan on the synthesis of lactic acid. The results obtained confirm that oligochitosans can be used as stimulators of lactic acid synthesis based on lactose containing substrates industrial fermentation using L. bulgaricus starter cultures. Using GC-MS, it was demonstrated that the interaction of the studied concentrations of chitosan with L. bulgaricus leads to a slowdown in the synthesis of propanol, an increase in the content of unsaturated and saturated fatty acids, and a change in the composition and content of other secondary metabolites. The quantity of L. bulgaricus in a sample with 0.01% chitosan exceeded their content in the control sample by more than 1,700 times. At the same chitosan concentration, the fermentation process was slowed down, increasing the shelf life of the fermented milk product from 5 to 17 days while maintaining a high content of L. bulgaricus (6.34×10 6 CFU/g) at a high content of biologically active substances, low concentration of lactic acid and the best sensory characteristics among studied samples. The concentrations of chitosan used did not give astringent taste to the fermented dairy product.